ANALISIS PERMAINAN BUNYI DENGAN PERBANDINGAN PEMAKAIAN MAJAS PERSONIFIKASI DALAM KAJIAN ANTOLOGI PUISI SULUK BAGIMU NEGERI - Hutabarat, Yunita Theresia Hutabarat (Hasta Wiyata, 2024)
Poetry is a literary work by applying dialect rules and structured patterns to the point where it creates both a compound and a sound in each syllable order that creates a wonderful impression. The comparative use of makeup in this study is still expressive. Expressive is a comparative phrase for a poem to be more interesting and have a message implied by the author. This approach to the study of poetic analysis uses qualitative descriptive analysis by taking a number of data comparison analyzes and thoughts from book analysis. The analysis of poetry covers the aspect of the sound play in the form of anaphora, kakofoni, euphoni, alliteration, and the style of comparative inanimate objects applied as if they were living. Personification majas describe the proper nature of human beings so characteristic of the poetry of panca indra by exposing the author's imagination. The study of Anthology of Suluk poetry to You Country contains the anxiety that is meant to bear the burden of death. The poem is unique to a more specific update in Islamic literature. The personification of the language style of poetry to your country is applied as the formulation of an object as if it were alive and given life as human nature as if it could speak, walk, speak with humanity